Erosive stability channel factor for Brda River (Poland): A key assessment of the human impact of the catchment changes - Dawid Aleksander Szatten; Oleksandr Obodovskyi; Marta Brzezińska (International Journal of Sediment Research)
The stability of river channels results from the impact of spatially diversified natural characteristics of the catchment, which are additionally intensified by the pressure of human activities. The aim of the current study was the overall assessment of the riverbed stability in the Brda River catchment (Poland) in the two periods 1980–1989 and 1991–2018. The study area is characterized by a high discharge regularity, resulting from the river-lake system in the upper part of the catchment, and strong human pressure caused by the presence of hydrotechnical structures in the middle and lower parts of the catchment. The hydrological, sedimentological, and land cover archival data were used in the current study. Also, in the field campaign, the characteristics of the river channel were delimited. Finally, the erosive stability channel factor is proposed, reflecting the level of pressure on the fluvial system from the catchment. The results show that in the first period, there was a tendency to accumulate sediment on the riverbed, resulting in its instability. However, in the second period, the river channel was stable, and erosion and sedimentation processes did not occur. The links between the stability of the bed of the Brda River, and the temporal and area-related pressures made it possible to identify long-term trends in the degradation of the fluvial environment as a result of human activities and to indicate the directions for sustainable sediment management in the catchment.